(untitled) (PJDOL, 2023)
The usage of various media methods in distance education shows its historical development path. It is said that AIOU has been using radio and television broadcasts, special textbooks and reading materials for distance education. To assess the level of technology usage and its role in AIOU model, Non-Random, Purposive Sampling, technique was used to choose the sample of 54 respon